The geological heritage of Tundavala (Angola): an integrated approach to its characterisation - Henriques, Maria Helena (2013)
This paper presents the results obtained using a qualitative assessment approach to characterise the geological heritage of Tundavala (Huila, Angola), needed in order to support a future classification proposal for the territory to ensure its preservation, as well as to promote geotourism, thus contributing towards sustainable local development. In order to characterise the geological heritage of Tundavala a set of various types of data for the different contents displaying heritage value was collected and processed. It was analysed in an integrated manner, taking into consideration data on the meanings attributed to Tundavala by scientific communities (degree of relevance), and public perceptions of such meanings (abstract perceptiveness). The results allow us to recognise in Tundavala, an object displaying heritage value, more than one type of content – documental, symbolic and scenic – which provides it with a degree of regional relevance and enhances its value as an element that incorporates the geological heritage of the earth. The methodologies used to characterise the geological heritage of Tundavala are independent of any national, regional and/or local legislation on geoconservation, whether they exist or not, and thus represents a useful tool for evaluating geological heritage in any place on earth, particularly in countries and/or regions where local geological knowledge is sparse and/or there is little public awareness of geoconservation.